Portal Hypertension Promotes Bacterial Translocation in Rats Mono- and Non Mono-Associated with Escherichia Coli C25. Issue 2 (1994) - Vauthey, Jean-Nicolas; Duda, Petra; Wheatley, Anthony M.; Gertsch, Philippe
Abstract : The basis for the high incidence of infectious complications in portal hypertension (PHT) remains unclear. The hypothesis that PHT induces bacterial translocation (BT) was tested in a rat model with or without mono-association with streptomycin resistant Escherichia coli C25 and with or without hypovolemic shock. PHT was achieved by partial portal vein ligation and three weeks later hypovolemic shock (HS) was induced. Blood, liver, spleen and mesenteric lymph nodes cultures were performed twenty-four hours later. PHT promoted BT to mesenteric lymph nodes in indigenous flora (4/6 [67%]) and mono-associated animals (7/9 [78%]) compared to sham laparotomy and sham shock (SL + SS) animals (0/6 [0%] and 2/9 [22%] respectively) ( p = 0.03). The combination of PHT and HS resulted in increased mortality in mono-associated (7/15 [47%]) and non mono-associated animals (8/15 [53%]). No significant translocation was noted in liver and spleen and bacteremia was found only in the PHT + HS mono-associated animals (4/8 [50%]). PHT induces BT to mesenteric lymph nodes and this may account for the high incidence of septic complications associated witti PHT. In this model, the addition of HS to PHT leads to an increased mortality but without uniform translocation of the gut flora beyond mesenteric lymph nodes.